Mengelola Manajemen Persediaan UMKM dalam Upaya Meminimalkan Risiko Terjadinya Pemborosan Biaya Persediaan - Erni Widajanti; Sutarno Sutarno (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Raw material inventory is crucial for the production process, therefore it must be managed properly. In MSMEs, raw material inventory is usually not managed properly, as is the case with MIZAN Bandung Toast UMKM. The owner who is also the manager has not controlled his raw materials, where the owner purchases raw materials only based on habit. For this reason, this community service activity was carried out with the aim of helping the owner who is also the manager of MIZAN Bandung Toast UMKM to manage his inventory, especially the raw material inventory in order to streamline raw material inventory costs. This community service activity was carried out using the counseling method followed by mentoring. In this mentoring activity, inventory control was carried out using the Economic Order Quantity (EOQ) method and the Just In Time (JIT) method. The activity was carried out from June 26 to 30, 2025, starting at 12:00 to 14:00 at MIZAN Bandung Toast UMKM. The result of this activity is that the management of raw material inventory carried out by the owner (partner) is not yet efficient, to be able to streamline the cost of raw material inventory, partners can apply the EOQ method which can save costs by 45.6%, JIT which can save costs by 59.2%. The benefits of this activity are to help the owners and managers of MIZAN Home Industry Bread: 1) in managing inventory to obtain inventory cost efficiency 2) to calculate the level of inventory cost efficiency. 3) Determine the right inventory control method.